EFEKTIVITAS PLIOMETRIK TERHADAP PENINGKATAN KECEPATAN PEMAIN SSB JTS KOTA JAMBI U-13 - Rivki Nuri Yanda; Wawan Junresti Daya; Usni Zamzami Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of plyometric training in improving the speed of U-13 players at JTS Soccer School (SSB JTS) in Jambi City. Speed is one of the most important physical components in soccer because it supports acceleration, ball pursuit, and competitive performance during matches. This research employed a quantitative method with an experimental approach using a One Group Pretest-Posttest Design. The population consisted of 30 U-13 players of SSB JTS Jambi City, all of whom were selected as research samples using the total sampling technique. The instrument used was a 30-meter sprint test to measure players' speed performance. The plyometric training program was conducted for four weeks with a frequency of three training sessions per week. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, and a paired sample t-test.The results showed that the average 30-meter sprint time decreased from 5.02 seconds in the pretest to 4.69 seconds in the posttest, resulting in an average improvement of 0.33 seconds. The normality test indicated that the data were normally distributed (Sig. = 0.200 > 0.05), while the homogeneity test showed homogeneous data (Sig. = 0.312 > 0.05). The hypothesis test produced a t-value of 18.75 with a significance value of 0.000 (p < 0.05). Therefore, it can be concluded that plyometric training has a significant and effective effect on improving the speed of U-13 players at SSB JTS Jambi City.